Signature change in spherical vacuum spacetimes - Sumeruk, H A (Department of Mathematics and Applied Mathematics, 2016)
This thesis follows the approach of papers (1, 2) by exploring signature changes in other metrics. The metrics we chose to investigate are the Schwarzschild metric and the Tolman metric. The Schwarzschild metric was originally chosen in order to investigate whether the neighborhood of the singularity inside a black hole can be replaced with a Euclidean region, and also to see whether this Euclidean region can lead to new universes by providing "wormholes" through to other Lorentzian universes. By this we mean that, if one follows "time-like" geodesic paths from a Lorentzian region into a Euclidean region, they bounce (instead of hitting a singularity) and can then pass through a second signature change into another Lorentzian region. Consideration of how geodesics pass through a signature change naturally leads to the Tolman metric, whose vacuum cases cover the Schwarzschild/Kruskal-Szekeres manifold with all possible sets of radial geodesic coordinates. We take the opportunity to explore several cases of signature change in other Tolman models.